Central bank digital currency: A review and some macro-financial implications - Chen, Hongyi; Siklos, Pierre L. (Journal of financial stability, 2022)
Central Bank Digital Currencies (CBDC) have attracted considerable interest and its deployment on a global scale is imminent. However, CBDC face several challenges. They include: legal, technological, and political considerations. We summarize those challenges and add a few more that have not received much attention in the literature. We then focus on two forms of CBDC: a narrow version that only replaces notes and coins and a broader form with a deposit feature. The narrow CBDC is the most likely one to be first introduced. Next, relying on evidence of past episodes of financial innovation, and using cross-country data, we explore the hypothetical impact of CBDC on inflation and financial stability, based on the historical behaviour of the velocity of circulation and incorporating a CBDC’s impact using McCallum’s policy rule which sets the stance of monetary policy based on money growth. Our simulations suggest that CBDC need not produce higher inflation, but financial stability remains at risk. We provide some policy implications. •We explore the macroeconomic impact of a digital currency (CBDC).•An open question is the impact of CBDC on the monetary transmission mechanism.•Simulations of a policy rule is used for understanding macroeconomic impact of CBDC.•We conclude that CBDC need not impair inflation control.•CBDC may not be a solution for dealing with major financial crises.